Medical Imaging 2023: Image Processing 2023
DOI: 10.1117/12.2654125
|View full text |Cite
|
Sign up to set email alerts
|

Semi-supervised clustering for neuro-subtyping of autism spectrum disorder

Abstract: Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder with heterogeneous symptoms and neural characteristics, which has hindered the finding of reliable biomarkers. Until recently, ASD subtyping using neuroimaging has emerged to detect underlying neural features in each subgroup. However, not only the existing findings are preliminary, but also the methodologies are diverse with no conclusions on which are superior. In this study, we implemented neurosubtyping of ASD using a semi-supervised c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(30 reference statements)
0
0
0
Order By: Relevance
“…These capabilities have aided in addressing the heterogeneity of psychiatric diseases and advancing the development of precision medicine in psychiatry. Many studies have demonstrated the existence of consistent functional connectivity patterns across subgroups, thus providing further support for the subdivision of psychiatric disorders into specific subtypes [34][35][36][37][38][39][40][41]. Additionally, graph theory approaches have been used to detect transdiagnostic biotypes of psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…These capabilities have aided in addressing the heterogeneity of psychiatric diseases and advancing the development of precision medicine in psychiatry. Many studies have demonstrated the existence of consistent functional connectivity patterns across subgroups, thus providing further support for the subdivision of psychiatric disorders into specific subtypes [34][35][36][37][38][39][40][41]. Additionally, graph theory approaches have been used to detect transdiagnostic biotypes of psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%